(untitled) (Palíndromo, 2023)
This paper approaches the making of artist’s books as decolonial practice. We address this topic by telling the story of the birth of the artist’s book ninharia and the bemvinda publisher. From the transmission of this experience, we understand that writing and books contain a colonial heritage - that of who can write and publish. We claim with Silvia Rivera Cusicanqui, however, a ch’ixi perspective as a methodology for approaching the artist’s book. Ch’ixi means the gray color in Andean weaving formed by white and black stripes that do not mix. In a culture founded on the principle of miscegenation such as ours, affirming ch’ixi is affirming the contradiction and the constant presence of alterity in identity and hegemonic forms. We hypothesize that the artist’s book can be an object in which words and forms of expression act as decolonial practices. In this sense, the independent publication can assume a political and ethical position in the war of denominations, as Antônio Bispo calls it, creating images, symbols, imaginaries, and desires that converge in the care of life.